NON-HIGH DENSITY LIPOPROTEIN CHOLESTEROL (NON-HDL-C)-A CORONARY RISK FACTOR - Tauheed, Shoaib; Shoaib, Shaheen; Haque, M. Naeem-ul (Journal of Ayub Medical College Abbottabad, 2003)
Background: Ischaemic heart disease (IHD) is influenced by elevated cholesterol, low density lipoproteins-C (LDL-C), triglycerides and low blood levels of high density lipoproteins (HDL-C). Recently, non-HDL-C has also been suggested as one of the factors involved in IHD. Non-HDL-C is the difference between total cholesterol and HDL-C. Assuming that non-HDL-C levels are raised in IHD, a cross sectional study was designed to evaluate the levels of non-HDL-C in patients of IHD. Methods: Thirty adult non-smoking male (age 50±0.51 years) patients of IHD were compared with 30 adult non-smoking males (47.27±1.15 years) controls without IHD. A 12 hours fasting blood sample was analysed to determine serum cholesterol and HDL on autoanalyzer. Results: Non-HDL-C was significantly raised (p<0.001) in patients of IHD when compared to controls. Values of non-HDL-C were 158.00±4.79 and 127.63±2.82 (Mean±SEM) in patients and controls respectively. Conclusion: Non-HDL-C contains all known potentially atherogenic lipid particles including LDL-C, intermediate density lipoproteins and very low density lipoproteins cholesterol remnants. Results of this study suggest it’s possible involvement in IHD. Non-HDL-C is an emerging a coronary risk factor. It is a cost effective screening test that may be included in coronary risk profile.